The Relationship Between Environmental Sanitation And The Incidence Of Environmentally Based Diseases - Nurul Aisyiyah Puspitarini; Muslimin B; Yermi Yermi (International Journal of Health Sciences, 2026)
Environmental sanitation is an important factor in maintaining public health and preventing the occurrence of environmentally related diseases. Poor sanitation can be a medium for transmitting various diseases, such as diarrhea, skin diseases, and respiratory infections. This study aims to determine the relationship between environmental sanitation and the incidence of environmentally related diseases. The study used an observational analytical design with a cross - sectional approach. The study sample consisted of 120 heads of families selected using a purposive sampling technique. Data were collected through questionnaires and environmental sanitation observation sheets, then analyzed using the Chi- Square test. The results showed a significant relationship between environmental sanitation and the incidence of environmentally related diseases (p < 0.05). It was concluded that poor environmental sanitation increases the risk of environmentally related diseases. Efforts to improve environmental sanitation and provide ongoing public health education are needed.